Sustainable landscape assessment of river catchments in the example of dikmen brook in Ankara, Turkey - Sahìn S. (Interdependency between agriculture and urbanization: Conflicts on sustainable use of soil and water, 2001)
In this paper a methodology is developed on landscape assessment for river catchments in the example of Dikmen Brook in Ankara. The method is the constructive part of the 'National Approach for Catchment Management' which is produced as a model for Turkey by this work. Landscape assessment is identified by NRA (1993) as an approach to analyse the landscape and accordingly to produce recommendations for the protection, management and improvement. In Turkey, a comprehensive national planning and management approach for urban and rural river systems is non-existent. Land-use decisions are generally produced in accordance with the socio-economic requirements and political reasons, and natural landscape elements (soil, vegetation cover, wildlife, climate, etc.) and processes (soil losses, hydrological cycle, etc.) are frequently neglected. Consequently, the landscape features are lost and also environmental problems arise due to mal-function of ecosystem, particuiarly in the areas where urbanisation is extensive.
Seminar: Interdependency between Agriculture and Urbanization: Conflicts on Sustainable Use of Soil and Water, 2000/04/02-06, Tunis (Tunisia)